Peran dan Kontribusi Ilmuwan Muslim dalam Pembelajaran Matematika - Dini Palupi Putri (ARITHMETIC: Academic Journal of Math, 2019)
The life that is lived now and in the future cannot be separated from the role of history in the past. Mathematics learning plays an important role in everyday life, often we find problems in everyday life can be solved with mathematical concepts. In learning mathematics, mathematical scientists contribute greatly to the learning of mathematics and mathematical concepts. It cannot be denied, in the golden age of Islam many Muslim scientists sprang up, including mathematical scientists. Muslim mathematicians who were very famous, one of them was al- Khawarizmi. The branch of science in mathematics put forward by al- Khawarizmi is Algebra. Algebra is very much used in the life of the current global era. Algebra is found in many daily activities, such as buying and selling, Mawaris knowledge, and so on. al- Khawarizmi is also an inventor of zeros and the originator of the concept of algorithms. In addition, this paper will discuss the contribution of scientist Ibn al- Haytham to the concept of absolute value, al- Biruni towards the concept of "The Broken Chord" theorem, al- Khayyami on the concept of geometry. The mathematical concepts found by scientists are what we use a lot today to solve problems used in everyday life.